How to Improve Taxes and Transfers in Israel - Hemmings, Philip (OECD Publishing, 2014)
Ensuring tax and transfer systems bring sufficient revenue to reach macroeconomic fiscal targets, address societal goals in re-distribution and social welfare, recognise the influence taxation has on businesses' competitiveness and adequately address environmental externalities is a tough challenge, arguably more so in Israel than in many other OECD countries. High interest payments and large defence spending make deficit and debt reduction more difficult, socio-economic divides remain wide and as a small-open economy Israel is highly exposed to mobile international capital and competition over international investment. And, as elsewhere, the incorporation of environmental issues into the tax system remains only partial. This review examines ways forward for policy on several fronts: indirect taxation; household income tax and social benefits; taxes on property and wealth; business taxation; and evasion, avoidance and administration issues. This Working Paper relates to the 2013 OECD Economic Review of Israel (www.oecd.org/eco/surveys/economic-survey-israel.htm)
Keywords: Taxation; Economics; Israel